Pengetahuan Keluarga tentang Pencegahan Malaria pada Anak - Kody, Martha Meti (Poltekkes Kemenkes Kupang, 2021)
Backgrond: Malaria remains a significant public health issue every year, primarily due to the lack of a vaccine for its prevention. In 2021, the number of malaria cases recorded in East Sumba Regency was 691. Objective: The aim of this study is to determine the knowledge and attitudes of families regarding malaria prevention in children in Temu Subdistrict, RT 33 RW 09, East Sumba Regency. Methods: This research uses a qualitative approach with a descriptive method, and the sampling technique applied is accidental sampling, with 30 respondents. The instrument used is a questionnaire. Results: The findings indicate that the knowledge and attitudes of families about malaria prevention in children in Temu Subdistrict, RT 33 RW 09, East Sumba Regency were as follows: 18 individuals (60%) had good knowledge, 6 individuals (20%) had adequate knowledge, and 6 individuals (13.3%) had poor knowledge. Regarding attitudes, 19 individuals (63.3%) demonstrated good attitudes, while 11 individuals (36.6%) had less favorable attitudes. The total number of malaria cases in East Nusa Tenggara (NTT) was 2,393, representing 2.5% of total cases, while East Sumba recorded 691 cases (1%) in November 2021.